Factors affecting implementation of client service charter in Tanzania local government authorities: A case of Bagamoyo district council - Raphael, Theresia (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the degree of Master of Science in Human Resource Management (MSc. HRM) of Mzumbe University